Peran Manajemen Sumber Daya Manusia dalam Mencapai Tujuan Strategis Perusahaan - Selti Sella; Hendra Riofita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Human Resource Management (HRM) plays a crucial role in achieving company strategic goals, especially amidst the challenges of globalization and increasingly fierce competition. This journal discusses the importance of effective HR management in creating competitive advantages and improving organizational performance. With a focus on talent development, employee welfare, and good relationships between management and employees, this research shows that good HRM practices can increase employee motivation, productivity, and loyalty. In addition, this journal highlights the need for strategies that are aligned with business goals to ensure that every individual in the organization contributes optimally. Through analysis of various challenges faced by HR management, including work-life balance and global skills development, this journal provides recommendations for increasing the effectiveness of HR management. It is hoped that the results of this research can become a reference for companies in formulating adaptive and innovative HR strategies, so that they can survive and develop in an era full of uncertainty.